Development of a shared decision-making intervention to improve drug safety and to reduce polypharmacy in frail elderly patients living at home - E. Drewelow; M. Ritzke; A. Altiner; A. Icks; J. Montalbo; V. Kalitzkus; S. Löscher; Y. Pashutina; S. Fleischer; J. Abraham; P. Thürmann; NK. Mann; et al. (Elsevier, 2022)
Objectives: For patients with geriatric frailty, reducing inappropriate medication is an important goal to improve patient safety in primary care. GP-side barriers include knowledge gaps, legal concerns, and lack of communication between the actors involved. The aim was to develop a multi-faceted intervention to facilitate deprescribing and shared prioritisation among frail elderlies with polypharmacy living at home. Methods: Mixed methods study including: 1) scoping review on family conferences, expert panels; 2) group discussions with GPs, mapping of needs and challenges in Primary Care; 3) workshops and expert interviews with GPs, patient advocates, researchers as a basis for a theoretical intervention model; 4) piloting. Results: A major challenge for GPs is to conduct a productive discussion with patients and family cares on deprescribing and drug safety. A guideline for a structured family conference with a medication check and geriatric assessment was developed and proved to be feasible in the pilot study. Conclusion: The intervention developed to facilitate deprescribing and shared prioritisation of drug therapy based on family conferences seems suitable to be tested in a subsequent cRCT. Innovation: Adapting family conferences to primary care for frail patients with polypharmacy.